2018
DOI: 10.1002/etep.2646
|View full text |Cite
|
Sign up to set email alerts
|

Renewable energy source-based multiarea AGC system with integration of EV utilizing cascade controller considering time delay

Abstract: Summary Automatic generation control of the unequal 3‐area system with diversified sources like small hydrothermal units in area‐1 and area‐2 and split shaft gas turbine thermal units in area‐3 with nonlinearity of generation rate constraint is explored. A cascade combination of integer order integral‐derivative with filter (IDN) and fractional order proportional derivative (FOPD) is considered as a secondary controller (IDN‐FOPD). The controller gains and other parameters are optimized using whale optimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 23 publications
0
53
0
Order By: Relevance
“…Raju et al reported the issue of LFC of MAPS with distributed generation resources, using a hybrid Ant-Lion Optimizer (ALO) pattern search optimization technique [38]. The LFC of a power system with electric vehicles was discussed by A. Saha in [39]. Here, electric vehicle system was integrated and the effect of cascade controller was studied.…”
Section: Lfc In a Maps With Conventional Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Raju et al reported the issue of LFC of MAPS with distributed generation resources, using a hybrid Ant-Lion Optimizer (ALO) pattern search optimization technique [38]. The LFC of a power system with electric vehicles was discussed by A. Saha in [39]. Here, electric vehicle system was integrated and the effect of cascade controller was studied.…”
Section: Lfc In a Maps With Conventional Sourcesmentioning
confidence: 99%
“…LFC in conventional power system with single area Contemporary technologies for energy storage; behavior of the load; impact of data latency on LFC; algorithms for optimal tuning of LFC [23][24][25][26] LFC in conventional power system with two area Multi-source two area power system with PI controller; reliability concerns; whale optimization algorithm; multi-source power system with PV and wind turbine; electric vehicle with LFC challenges; multiple sources and the related challenges; intelligent controller for AGC [27][28][29][30][31][32][33] LFC in conventional power system with multiple area controllers for LFC of MAPS; flower pollination algorithm; wind driven optimization algorithm for LFC; GRC with nonlinearity; stochastic fractional search algorithm for LFC; hybrid ALO pattern search optimization; effect of cascade controller on electric vehicles; security concern related to LFC [34][35][36][37][38][39][40] LFC in power system with renewable sources social spider optimizer technique; LFC for multi micro grid power system; improvisation of swarm optimization technique; grasshopper optimization technique; intelligent optimization techniques with renewable sources [41][42][43][44][45][46][47][48][49] Advancements in controllers for LFC of power system…”
Section: Domain Key Problems Addressed Referencesmentioning
confidence: 99%
“…The modelling of open market multi-source power system presented in [40][41]. In the structure of deregulated power system each area consisting of thermal-hydro combination.…”
Section: Deregulated Power System Modelmentioning
confidence: 99%
“…In the structure of deregulated power system each area consisting of thermal-hydro combination. The modelling of multi area deregulated power system presented in [40,41]. The poles and zeros are established by the (11) (12) 2N+1 is the order of filter and , are the lower and higher cut-off frequencies (13) Fractional Order derivative and integral is linear operator as given in equation 14, 15) (14(15)…”
Section: Deregulated Power System Modelmentioning
confidence: 99%
“…However, the coordinated frequency and voltage regulation of a 50‐Hz frequency‐based isolated hμG are unexplored so far. Again, most of the earlier works 27‐29 are focused on active power balance of a 60‐Hz–based system with ALFC, whereas this work focuses on apparent power balance introducing a novel integral square of weighted absolute error function (ISWAE). Hence, this work is motivated towards putting an earliest effort to study the performances of proposed (50‐Hz–based) hμG with PID controllers, using a novel QSHO algorithm.…”
Section: Introductionmentioning
confidence: 99%